The Peri-Urban Gentrification Process in Cisauk Subdistrict, Tangerang Regency, Indonesia - Andini, Myla Dyan; Lestari, Forina; Medtry, M; Karenina, Anna (Universitas Muhammadiyah Surakarta, 2023)
Gentrification is a phenomenon that occurs in many regions. Gentrification is characterized by the influx of more affluent residents into initially low-value areas. This influx increases the value of these areas, potentially leading to the displacement of people who cannot afford to remain in the neighborhood. This study aims to examine the cause and impacts of peri-urban gentrification in Cisauk District, Tangerang Regency. This study uses qualitative and remote sensing-based analysis to investigate gentrification's impact on six Cisauk sub-district villages. We used primary and secondary data for the analysis. The primary data was collected from observations, interviews, questionnaires, and Google Earth Engine data catalog to get Landsat 7 and 8 image-ries. The secondary was collected from the Central Bureau of Statistics. The Landsat data was used to identi-fy the change on the physical aspect, while the others were used to analyze the non-physical aspect. After-ward, positive and negative effects were explored, emphasizing residents' responses and adaptations. The re-sults showed that Cisauk Subdistrict faced a gentrification process driven by locational factors (i.e., proximity to toll road) and local government policies (i.e., spatial planning policy designating it as a high-density residential area). The positive impact of the gentrified area is that the region is developing economically much better, and many areas function better economically and so benefit the region and its people. On the other hand, the negative impacts of gentrified areas are that indigenous people are threatened with being forced to leave their villages, there are significant increases in land prices, and changes in people's social lives occur. To minimize the negative impact of gentrification, the government should promote the capacity of low-income households to access its benefits.